2004
DOI: 10.1128/jcm.42.3.1016-1023.2004
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Mediated Heteroduplex Analysis for Detection of pncA Mutations Associated with Pyrazinamide Resistance and Differentiation between Mycobacterium tuberculosis and Mycobacterium bovis by Denaturing High- Performance Liquid Chromatography

Abstract: The goal of this study was to apply temperature-mediated heteroduplex analysis using denaturing highperformance liquid chromatography to identify pyrazinamide (PZA) resistance in Mycobacterium tuberculosis isolates and simultaneously differentiate between M. tuberculosis and Mycobacterium bovis. Features that contributed to an optimal assay included the use of two different reference probes for the pncA gene targets from wild-type M. tuberculosis and wild-type M. bovis, optimization of the column temperature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 30 publications
0
8
1
Order By: Relevance
“…Similar problems are expected for any molecular technique that probes for DNA alterations in pncA, probably including sequencing. For instance, Mohamed et al (25) reported problems detecting a 1-bp deletion within codon 24 using denaturing high-performance liquid chromatography. Branch migration inhibition (18) and single-stranded conformation polymorphism (6,34) have also been used to detect pncA mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Similar problems are expected for any molecular technique that probes for DNA alterations in pncA, probably including sequencing. For instance, Mohamed et al (25) reported problems detecting a 1-bp deletion within codon 24 using denaturing high-performance liquid chromatography. Branch migration inhibition (18) and single-stranded conformation polymorphism (6,34) have also been used to detect pncA mutations.…”
Section: Discussionmentioning
confidence: 99%
“…The "bubble" type is formed between DNA fragments with single base differences and the bulge type is formed when there are deletions or insertions present within the two fragments. Recently, temperature mediated HA has been applied to the detection of mutations associated with mutations in rpoB, katG, rpsL, embB and pncA genes (Mohamed et al, 2004;Cooksey et al, 2002). Neither HA nor the SSCP analysis are 100% sensitive although Rosetti et al found that HA detected more mutants (Nataraj et al, 1999).…”
Section: Heteroduplex Analysis (Ha)mentioning
confidence: 99%
“…Double point mutation of gyrA is relatively rare (2,5,12) and is generally thought to be uncommon in clinical isolates. The Ala 74 Ser mutation has been reported only for other bacteria (8,12). This indicates that fluoroquinolone resistance is already emerging in China.…”
mentioning
confidence: 99%
“…DHPLC is a relatively new technique utilizing heteroduplex formation between wild-type and mutated DNA strands to identify mutations and was predicted to be a potentially useful genotypic screening method for gene mutations conferring drug resistance in M. tuberculosis (3,8,10). In this study, by introducing M. tuberculosis H37Rv and M. tuberculosis Erdman as two reference strains, the interference from the codon 95 AGC3ACC natural polymorphism was successfully avoided.…”
mentioning
confidence: 99%